Barcodes of marine invertebrates from north Iberian ports: Native diversity and resistance to biological invasions. Issue 1 (15th November 2016) - Miralles, L.; Ardura, A.; Arias, A.; Borrell, Y.J.; Clusa, L.; Dopico, E.; de Rojas, A. Hernandez; Lopez, B.; Muñoz-Colmenero, M.; Roca, A.; Valiente, A.G.; Zaiko, A.; et al.
Abstract: Ports are gateways for many marine organisms transported by ships worldwide, especially non-indigenous species (NIS). In this study carried out in North Iberian ports (Cantabrian Sea, Bay of Biscay) we have observed 38% of exotic macroinvertebrates. Four species, namely the barnacle Austrominius modestus, the tubeworm Ficopomatus enigmaticus, the Pacific oyster Crassostrea gigas and the pygmy mussel Xenostrobus securis, exhibited clear signs of invasiveness. A total of 671 barcode (cytochrome oxidase subunit I or 18S rRNA) genes were obtained and confirmed the species status of some cryptic NIS. Negative and significant correlation between diversity estimators of native biota and proportion of NIS suggests biotic resistance in ports. This could be applied to management of port biota for contributing to prevent the settlement of biopollutants in these areas which are very sensitive to biological invasions. Highlights: Marine biological invasions often use ports as gateways. Fouling macrobiota was sampled from eight ports within south Bay of Biscay. DNA barcoding helped to identify phenotypically plastic species. Negative correlation between native biodiversity and frequency of exotics was found. Results suggest native biodiversity protects against invasions in ports.